2019
DOI: 10.29252/ijca.1.1.15
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Distraction Techniques (Bubble and Cartoon) On Reducing Chemotherapy induced pain in children with Cancer

Abstract: Introduction:: The purpose of the present study was to compare the influence of the two techniques of distraction through watching a cartoon and bubble manufacturing /producing on chemotherapy pain reduction in children suffering from cancer. Method: The method of the study was pretest and post test experimentation with the control group. The study population included all children with cancer hospitalized in Buali hospital in Ardabil. The subjects were selected through convenience sampling method and were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
1
7
0
2
Order By: Relevance
“…The intra-spinal injection of chemotherapy drugs is associated with pain in children with cancer, and various studies have depicted that distraction therapy is effective in reducing pain (10,16,17). Mitigating anxiety and pain, distraction allows patients to have deeper breathing; this, in turn, can enhance SaO 2 (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intra-spinal injection of chemotherapy drugs is associated with pain in children with cancer, and various studies have depicted that distraction therapy is effective in reducing pain (10,16,17). Mitigating anxiety and pain, distraction allows patients to have deeper breathing; this, in turn, can enhance SaO 2 (18).…”
Section: Discussionmentioning
confidence: 99%
“…The mean pain intensity was significantly lower in the intervention group than in the control group. In a study on 48 cancerous children admitted to Bouali Hospital in Ardabil (Iran), Mikaeili et al (17) inferred that the mean pain score was significantly lower in the bubble-making group than in the group watching the cartoon; moreover, the mean pain score was significantly higher in the control group than in the two intervention groups. These results demonstrate that distraction techniques (cartoon watching and bubble making) help relieve children's pain during chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the method of visual distraction using video games reduced the pain of burn dressing change in children aged 3-6 years (Kaheni et al, 2016). Mikaeili et al (2019) studied the effect of watching cartoons and making bubbles in reducing pain caused by chemotherapy in all children with cancer. They found that there was a statistically significant difference in the mean pain intensity between the bubble-making and cartoon-watching groups and between both test groups and the control group.…”
Section: Painmentioning
confidence: 99%
“…The results also show that the method of making bubbles more than watching cartoons helps reduce children's pain during chemotherapy. The researchers concluded that the distraction method is one of the nonpharmacological interventions effectifve in re; eving pain (Mikaeili et al, 2019). Hua et al (2015) examined the effect of distraction with the help of virtual reality on reducing pain during dressing in children with chronic lower limb ulcers.…”
Section: Painmentioning
confidence: 99%
See 1 more Smart Citation